1986
DOI: 10.1007/bf00250518
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of two patent strains of Zymomonas mobilis in batch and continuous fermentations

Abstract: SummaryThe performance of Zymomonas mobilis strains ATCC 31 821 and ATCC 31 823 was assessed in batch and continuous culture. In batch culture using a medium containing 250 g/1 glucose, identical maximum specific growth rates of 0.16/h were found, though final biomass concentration and growth yield were significantly lower for ATCC 31 823 than for ATCC 31 821. Final ethanol concentrations in this medium were about 110 g/1 vor both organisms. In continuous culture at increasing dilution rates using a medium con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The performance evaluation of two strains of Z. mobilis (ATCC 31 821 and 31 823) in batch and continuous culture indicated that specific kinetics of both strains was very similar with respect to both glucose uptake and ethanol production 38. The effect of glucose, fructose and sucrose on the fermentation kinetics in batch cultures of Z. mobilis NRRL B‐4286 showed that the increase in substrate concentrations strongly affect the parameters related to growth rather than those related to ethanol production 39…”
Section: Substrates For Ethanol Productionmentioning
confidence: 99%
“…The performance evaluation of two strains of Z. mobilis (ATCC 31 821 and 31 823) in batch and continuous culture indicated that specific kinetics of both strains was very similar with respect to both glucose uptake and ethanol production 38. The effect of glucose, fructose and sucrose on the fermentation kinetics in batch cultures of Z. mobilis NRRL B‐4286 showed that the increase in substrate concentrations strongly affect the parameters related to growth rather than those related to ethanol production 39…”
Section: Substrates For Ethanol Productionmentioning
confidence: 99%
“…Among bacteria, Z. mobilis has an exceptionally high ethanol tolerance and is capable of producing ethanol in concentrations up to 13% (w/v) [6]. Despite this fact, end-product inhibition by ethanol is clearly the main limiting factor for the overall efficiency of the fermentation process [48][49][50]. A search for the primary site of ethanol inhibition has led to a number of investigations on how ethanol affects catabolic enzymes and the cell membrane.…”
Section: Effects Of Ethanolmentioning
confidence: 99%